Review of nitrogen compounds prediction in water bodies using artificial neural networks and other models - Kumar, Pavitra; Sai, Hin Lai; Jee, Khai Wong; Mohd, Nuruol Syuhadaa; Kamal, Md Rowshon; Afan, Haitham Abdulmohsin; Ahmed, Ali Najah; Sherif, Mohsen; Sefelnasr, Ahmed; El-Shafie, Ahmed (MDPI, 2020)
The prediction of nitrogen not only assists in monitoring the nitrogen concentration in streams but also helps in optimizing the usage of fertilizers in agricultural fields. A precise prediction model guarantees the delivering of better-quality water for human use, as the operations of various water treatment plants depend on the concentration of nitrogen in streams. Considering the stochastic nature and the various hydrological variables upon which nitrogen concentration depends, a predictive model should be efficient enough to account for all the complexities of nature in the prediction of nitrogen concentration. For two decades, artificial neural networks (ANNs) and other models (such as autoregressive integrated moving average (ARIMA) model, hybrid model, etc.), used for predicting different complex hydrological parameters, have proved efficient and accurate up to a certain extent. In this review paper, such prediction models, created for predicting nitrogen concentration, are critically analyzed, comparing their accuracy and input variables. Moreover, future research works aiming to predict nitrogen using advanced techniques and more reliable and appropriate input variables are also discussed.